RANCANG BANGUN APLIKASI SPEECH TO TEXT BERBASIS ANDROID PADA ELEVENIA - Dadang Iskandar Mulyana; Irbah Baihaqi (CKI ON SPOT, 2021)
Online shop today is no longer a stranger to the people of Indonesia, whether in daily use the internet or not. With this online sale makes it easy for people to transact without having to go to the place of goods to be purchased. Before making a transaction, the user will first search for items to be purchased in the search system. Each user would want an innovation of any e-commerce applications that run for convenience when shopping and ease to transact. Search by voice allows users to search for items they want to buy in an online shop without having to type. Because in some cases found, not all users who want to shop online feel comfortable typing, they want a convenience. In addition to these conveniences there is a longer typing time than converter sound into text. An appropriate innovation to increase the user's comfort in finding the product they want to buy is by using speech to text technology, where only with one click record sound of goods to be searched and e-commerce will display products relevant to the keyword of the desired goods.With a search application with this voice or speech to text, will give the user the convenience of shopping online. Elevenia.co.id is one of the most popular e-commerce community that allows to adopt the application. If before Elevenia.co.id only provide keyword-based search, hopefully with speech to text application is expected to provide benefits on the parties Elevenia.co.id and to its users.